Perancangan Prototype Sistem Informasi Pembelian Barang pada Toko Furniture ZADA menggunakan Figma untuk Meningkatkan Efisiensi dan Akurasi - Firmansyah Firmansyah; Dani Setiyadi; Izza Nisa’ul Afi; Syahqim Sudarpo (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Toko Furniture ZADA is a business that heavily relies on the smooth process of purchasing goods from suppliers to maintain stock availability and ensure the operational efficiency of the store. However, the manual purchasing record system has led to several issues, such as the risk of data loss, delayed entries, and errors in report preparation. These issues hinder operational effectiveness and could lead to financial losses. Therefore, this research aims to design a prototype of a purchasing information system that meets the operational needs of Toko Furniture ZADA in a more efficient, accurate, and timely manner. The design of this information system is carried out using a prototyping approach, utilizing Figma as a design tool, which allows for the creation of an interactive system interface that can be directly tested by users. The designed system includes several key features that are essential for the smooth operation of the store. These features include user login for data security, stock management that automatically records incoming and outgoing items, purchasing transaction records that facilitate control and transparency in each purchase transaction, and a reporting system that provides real-time information on stock status and purchase transaction reports with higher accuracy. The results of this study show that the designed information system prototype provides an efficient, accurate, and user-friendly digital solution to replace the existing manual process. The implementation of this system is expected to reduce the risk of data loss, avoid delays in recording, and improve the accuracy of report preparation. Additionally, the system can accelerate the purchasing process and stock management, which in turn will enhance the overall operational effectiveness and efficiency of Toko Furniture ZADA.